2020
DOI: 10.7897/2230-8407.110433
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Guar (Cyamopsis Tetragonoloba L.): A Cash Crop

Abstract: Guar is an essential legume domesticated mainly on marginal and sub marginal areas of arid and semi-arid regions. Generally, Pakistan yields around 15% of worldwidetotal guar production. Its area under cultivation is more than 0.181 million hectares in Pakistan. Regarding to its demand in the foreign market, it is cultivated in Punjab,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Like other legumes, guar is used in the national economy. M. Shakir et al (2020) indicated that guar cake, similar to soybean meal, is a separate additive to animal food due to its high crude protein content of about 480 g/kg dry matter.…”
Section: Introductionmentioning
confidence: 99%
“…Like other legumes, guar is used in the national economy. M. Shakir et al (2020) indicated that guar cake, similar to soybean meal, is a separate additive to animal food due to its high crude protein content of about 480 g/kg dry matter.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in view the pharmacological potential of cluster bean, the BR-99 is the locally available cultivar of cluster bean with maximum grain yield potential that is, 1900 kg ha −1 , and also provides 30 t ha −1 fodder yield in Pakistan (lqbal Saleem et al, 2002; Khan et al, 2018; Shakir et al, 2020), however, with very less phytochemical exploitation knowledge. The current study aimed with detail exploration of the phytochemical and biological potential of locally recognized with high yield and wide range of adaptation cluster bean (BR-99) cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the methanolic extract was found helpful in the therapeutic cure of anti-Parkinson's activity and motor dysfunction, owing to its anti-oxidants potential (Kaur and Saxena, 2021). The significant (99.99%) anti-viral potential of this plant was reported by Kaushik et al, 2020 tested against dengue-2-virus. Keeping in view the pharmacological potential of cluster bean, the BR-99 is the locally available cultivar of cluster bean with maximum grain yield potential that is, 1900 kg ha À1 , and also provides 30 t ha À1 fodder yield in Pakistan (lqbal Saleem et al, 2002;Khan et al, 2018;Shakir et al, 2020), however, with very less phytochemical exploitation knowledge. The current study aimed with detail exploration of the phytochemical and biological potential of locally recognized with high yield and wide range of adaptation cluster bean (BR-99) cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Cluster bean (Cyamopsis tetragonoloba L.) is a multipurpose leguminous crop, widely grown in the arid and semiarid regions of India (80%), Pakistan (15%), Sudan, USA, and SA (5%). [50][51][52] In Pakistan, around 15% of total worldwide cluster bean production generally, and more than .181 million hectares area for cluster bean production is cultivated mostly in Punjab, and Sindh province [53][54][55] . It has wide application from the food industry to textile, medicine, dyes or varnish, cosmetics, explosives, and petroleum industry.…”
Section: Introductionmentioning
confidence: 99%